Judarna och stadsbranden: Judisk invandring och integration i det sena 1800-talets Sverige - Hammarström, Per (Nordisk judaistik/Scandinavian Jewish Studies, 2008)
The purpose of this investigation is to analyze aspects of Jewish integration into Swedish society during the decades following the emancipation which was carried out in 1870, by means of investigating how a Jewish migrant group was given space and was able to participate in the local society. The study shows a Jewish middle class evolving and becoming integrated into society. This group which was forced to behave carefully and balance their Jewish and their Swedish identity, came to play an important role as a link between the receiving society and the rest of the Jewish population.